The role of religious education in the fight against HIV and AIDS in Botswana by promoting caring attitudes - Mmolai, Sana K. (Boleswa Occasional Papers in Theology and Religion, 2007)
Since the discovery of HIV and AIDS in the early 1980 's, education has been acclaimed as a global strategy for fighting against the spread of HIV and AIDS. In 1988 the Government of Botswana adopted a national AIDS policy which calls on the Ministry of Education to spearhead the fight against the spread of HIV and AIDS by infusing HIV and AIDS education into the curriculum at all levels of education.
Free